Mineral concentrations in milk from cows fed seaweed (Saccharina latissima) under different basal protein supplementation. (1st March 2023) - Qin, Nanbing; Pétursdóttir, Ásta H.; Humphries, David J.; Desnica, Natasa; Newton, Eric E.; Vanhatalo, Aila; Halmemies-Beauchet-Filleau, Anni; Bell, Luke; Givens, D. Ian; Juniper, Darren T.; Gunnlaugsdóttir, Helga; Stergiadis, Sokratis
Highlights: Effect of seaweed and rapeseed feeding on bovine milk minerals was investigated. Feeding seaweed increased milk I and reduced milk Ca and Co contents. Feeding rapeseed reduced milk Mn and I contents. Seaweed increases milk I but care is needed to avoid excess milk I content. I supplementation is recommended in rapeseed-fed cows to maintain I content. Abstract: Sixteen multiparous Holstein cows in four blocks of 4 × 4 Latin square over 4-week experimental periods were used to study the effects of seaweed ( Saccharina latissima ) supplement (with/without) and protein source (rapeseed meal (RSM)/wheat distiller's grain (WDG)) on milk mineral concentrations. Dietary treatments did not affect milk production and basic composition. Feeding seaweed slightly decreased milk Ca and Cu concentrations; whilst increased (by 3.3-fold) milk iodine (I) concentration, due to a higher dietary I supply. Substitution of WDG with RSM increased feed-to-milk transfer of Ca, Na, and Se and decreased that of Mg, P, Fe, and Mn; but only reduced milk Mn and I concentrations (the latter by 27 % as a potential result of increased glucosinolate intake). Seaweed supplement can improve milk I content when cows' I supply/availability is limited, but care should be taken to avoid excess milk I contents that may pose nutritional risks for young children.